The Effect of Providing Brochure Media, Educational Video, and Power point on Knowledge Food Processing Sanitation Hygiene (Studi on Roadside Traders in East Telukjambe District, Karawang) - Latifah Wardayanto; Ratih Kurniasari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Fulfillment of nutrients to obtain energy to support life and daily activities can be done through food consumption. Food should have a good impact on the body because the nutritional content can be dangerous if it is contaminated with harmful substances, one of which is snack food. To increase understanding of sanitary hygiene in food processing among traders, promotive efforts are therefore made through increasing knowledge in educational activities Objective: This research aims to determine the effect of providing educational media, namely Brochures, Educational Videos, Powerpoint regarding knowledge and practices of food hygiene and sanitation to traders in Teluk Jambe Timur Karawang District. Method: The method used in this paper is quasi-experimental with pre-test and post-test group design. The total sample of respondents in this study was 45 respondents who were selected by purposive sampling including three groups with educational treatment using brochure media, educational video media, and Powerpoint media. Statistical test data analysis was carried out with the Wilcoxon. Result: The results of the Wilcoxon test showed differences in knowledge regarding food processing hygiene and sanitation before and after education using brochure media (p-value = 0.001), video media (p-value = 0.004) and Powerpoint media (p-value = 0.001). Conclusion: The three media education, video media gave higher results compared to the other two media on the effect of increasing knowledge about food processing hygiene and sanitation.